Comparative Effects of Luteolin and Quercetin on Adipogenesis in 3T3-L1 Cells - Sakuma, Satoru; Yabuuchi, Midori; Yoshizumi, Ayumi; Okajima, Yui; Fujimoto, Yohko; Okuhira, Keiichiro (Journal of Pharmacy and Nutrition Sciences, 2021)
Purpose: Quercetin has been reported as a more potent inhibitor of fat accumulation than other flavonoids. However, little information is available regarding the strength and mechanism of the repressive action of luteolin on fat accumulation. Therefore, the aim of the present study was to evaluate the comparative effects of luteolin and quercetin on the differentiation of 3T3-L1 preadipocytes into mature adipocytes. Methods: 3T3-L1 preadipocytes were differentiated by treatment with insulin, dexamethasone, and 3-isobutyl-1-methylxanthine in the presence of luteolin or quercetin. Alterations in triacylglycerol (TG) levels, lipid-filled adipocyte quantity, and the mRNA and protein expression levels of CCAAT-enhancer-binding protein α (C/EBPα) and peroxisome proliferator–activated receptor γ (PPARγ) were measured. Results: Both luteolin and quercetin reduced TG levels, the number of lipid-filled adipocytes, and the mRNA expression levels of C/EBPα and PPARγ; however, these effects occurred with lower concentrations of luteolin than quercetin. Conclusions: These results suggest that luteolin may be more potent than quercetin in inhibiting adipocyte differentiation. These effects may be explained by differences in the inhibitory effects of the two compounds on C/EBPα and PPARγ expression. This study suggests that luteolin might be a beneficial dietary supplement for obesity and lifestyle-related diseases.